2010
DOI: 10.1007/s00592-010-0191-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychological adjustment to diabetes mellitus: highlighting self-integration and self-regulation

Abstract: Psychological adjustment to any chronic disease, such as diabetes mellitus, concerns self-view rearrangement toward self-integrity and self-regulation. Both distance between self and disease paired with positive and negative new identities may contribute to adaptation to diabetes. The present investigation aimed to detect main trends on self-management in patients with both diabetes types within a self-regulatory framework. Sample consisted of 121 adult patients with both diabetes types. Answer to question abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 22 publications
2
18
0
3
Order By: Relevance
“…Additionally, the results of the present research are in line with previous studies reporting the importance of such protective factors, namely psychosomatic health (Suris, Bélanger, Ambresin, Chabloz, & Michaud, 2011), resilience (Guilera, Pereda, Paños, & Abad, 2015;Helgeson, Reynolds, Siminerio, Becker, & Escobar, 2014;, self-regulation (Gois et al, 2012) and social support (Békési et al, 2011;Wu, Geldhof, Roberts, Parikshak, & Amylon, 2013). Resilience, social support, symptom's control and self-management may allow a good adaptation in adolescents, while facing adverse health conditions and potentially stressful new situations, and help to reduce stress, increase control and improve outcomes in HRQoL.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the results of the present research are in line with previous studies reporting the importance of such protective factors, namely psychosomatic health (Suris, Bélanger, Ambresin, Chabloz, & Michaud, 2011), resilience (Guilera, Pereda, Paños, & Abad, 2015;Helgeson, Reynolds, Siminerio, Becker, & Escobar, 2014;, self-regulation (Gois et al, 2012) and social support (Békési et al, 2011;Wu, Geldhof, Roberts, Parikshak, & Amylon, 2013). Resilience, social support, symptom's control and self-management may allow a good adaptation in adolescents, while facing adverse health conditions and potentially stressful new situations, and help to reduce stress, increase control and improve outcomes in HRQoL.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have described depression and diabetes as comorbid conditions and explored the association of depression with metabolic variables [1][2][3][4]. It is not clear, however, which comes first.…”
Section: Discussionmentioning
confidence: 99%
“…Background Several reports suggest that people with diabetes are almost twice as likely to suffer from depression and anxiety as the general population [1][2][3][4]. Emotional problems may influence patient adherence to lifestyle and treatment recommendations, be associated with decreased quality of life, impaired self-care behaviors, and poorer glycemic control [5] and contribute to increase health care costs [2].…”
Section: Introductionmentioning
confidence: 99%
“…Illness representation research on people with diabetes showed a consistent result towards adherence (Mann, Ponieman, Leventhal, & Halm, 2009), successful self-management (Bean et al, 2007) as well as a good psychological adjustment (Gois et al, 2010). Individuals who have poor control over diabetes have a different illness representation compared to individuals with good control over diabetes (Keogh et al, 2007).…”
Section: Introductionmentioning
confidence: 99%